"Smart vending machine" / Natasah Sudin, Ain Nadiah Ahmad and Hazirah Azami - Sudin, Natasah; Ahmad, Ain Nadiah; Azami, Hazirah (2018)
The problem statement of this study is to analyses the problem associated with the delivery matters of the frozen product by House of Frozen Company. The main problem of this company are the ordering system is not efficient. When the costumer want to order the food, the company have the problem to give response within the promise time. The method that the team use to collect data is interview method. Owner of House of Frozen company was being interviewed on 25/3/2018 in Seri Iskandar, Perak. However, the team only managed to get data for only one company. The limitation is the team do not get enough data from more frozen's food companies. So, the team are unable to capture the real problem that have been face by them. The team need longer time to collect data.